Comparison of Pedagogical Approaches as Perceived by the Teachers of Special and Regular Schools - Humara Bano, Maria Sohaib Qureshi, Munawar Ahmed Malik (JIE, 2024)
Pedagogy refers to the dynamic relationship between learning, teaching and culture. The present study was aimed to examine and analyze pedagogical understanding of the teachers about teaching methods. The sample of the study consisted of 200 teachers out of which 100 teachers were serving in special education institutes and 100 in general education institutes of Lahore city. Purposive sampling technique was used to select the sample.